Práticas relacionadas a indústria 4.0 e suas aplicações no campo da ergonomia: análise da implementação de exoesqueletos - Toniolo, Lucas Corrêa (Universidade Federal de São Carlos, 2023)
The 4th industrial revolution is a new trend that brought innovations to the corporate world, however, at the same time, it raised questions about workers' health, making the study of the relationship between technologies of that era and Ergonomics plausible. Thus, the objective of this study was to identify practices related to Industry 4.0 and its applications and contributions in the field of ergonomics and to systematize knowledge in order to assist companies in their acquisition and implementation processes. With this, an integrative review was carried out and from it the application of the multiple case study methodology was proposed. For this second stage, questionnaires were created in the form of semi-structured interviews and these were applied to four industry professionals who had contact and experience with the technologies studied, in this case, industrial exoskeletons. From the collection of interviews, data were processed and analyzed, culminating in three distinct cases that enabled a dialogue between literature and practice. Thus, the results generated in this study identified that practices related to industry 4.0, which are linked to the field of ergonomics, are not properly framed in the literature. Much of this is due to a managerial fad, the lack of studies on the technologies sold and an industry of managerialism behind this theme. Therefore, from the results of the investigation, a technocratic profile of approach was identified for the implementation of passive industrial exoskeletons, which culminated in the proposition of a theoretical model of application based on Conception Ergonomics from the perspective of the integrative approach.
Practices related to industry 4.0 and its applications in the field of ergonomics: analysis of the implementation of exoskeletons
Keywords: Industria 4.0; Ergonomia; Fatores humanos; Exoesqueletos; Industry 4.0; Ergonomics; Human factors; Exoskeletons; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO